(untitled) (Canadian Allergy & Immunology Today, 2022)
In the last decade, the advent of biologic medications has transformed the practice of allergy, allowing clinicians to address unmet needs in the treatment of asthma, chronic spontaneous urticaria, atopic dermatitis and nasal polyposis. Emerging and novel therapeutic agents in food allergy have however been slower to develop, with no biologic currently approved for this indication. One factor has been that the low direct cost associated with food allergy created a poor incentive for pharmaceutical investment in research and development. However, the recent availability of health economic tools to quantify intangible costs and the recognition of oral immunotherapy as a valid treatment alternative has helped better define the unmet need. This may partly explain the renewed interest in developing medications for food allergy, with ongoing trials at various stages. In practice, clinicians are confronted with severe and/or complex cases of food allergy that could potentially benefit from treatment with biologic therapy, but there are no published studies demonstrating their proper use in these clinical scenarios and patient populations. There are various review articles available summarizing the evidence from the literature. The objective of this article is to focus on practical knowledge regarding the off-label use of biologics in food allergies.